2022
DOI: 10.3390/ijerph19116671
|View full text |Cite
|
Sign up to set email alerts
|

Community Mobility and COVID-19 Dynamics in Jakarta, Indonesia

Abstract: In response to the COVID-19 pandemic, mobile-phone data on population movement became publicly available, including Google Community Mobility Reports (CMR). This study explored the utilization of mobility data to predict COVID-19 dynamics in Jakarta, Indonesia. We acquired aggregated and anonymized mobility data sets from 15 February to 31 December 2020. Three statistical models were explored: Poisson Regression Generalized Linear Model (GLM), Negative Binomial Regression GLM, and Multiple Linear Regression (M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The study found that Retail and Recreation have low mobility, but the Grocery, Pharmacy and Transit Stations have higher mobility. In our neighbouring country, Indonesia, the Grocery and Pharmacy is reported to be the highest (4.12%) in predicting COVID-19 dynamics (Nanda R.O. 2022).…”
Section: Community Mobility and Incidence Of Covid-19 During Lockdownmentioning
confidence: 76%
“…The study found that Retail and Recreation have low mobility, but the Grocery, Pharmacy and Transit Stations have higher mobility. In our neighbouring country, Indonesia, the Grocery and Pharmacy is reported to be the highest (4.12%) in predicting COVID-19 dynamics (Nanda R.O. 2022).…”
Section: Community Mobility and Incidence Of Covid-19 During Lockdownmentioning
confidence: 76%
“…Nevertheless, interest in many works has focused on the impact of COVID-19 on mobility, and few efforts have been directed at assessing how regulating mobility rates can have positive effects on controlling virus transmission. Examples of these studies have focused on Taiwan [ 6 ], Poland [ 7 ], the United States [ 8 ], India [ 9 ], Spain [ 10 , 11 ], Japan [ 12 ], the United Arab Emirates [ 13 ], Saudi Arabia [ 14 ], Greece [ 15 ], China [ 16 , 17 ], Indonesia [ 18 ], Austria [ 19 ], Italy [ 20 ], Portugal [ 21 , 22 ], South Africa [ 23 ], Costa Rica [ 24 ], and Australia [ 25 ], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Cooper et al [7] proposed a new model based on the SIR model, which is able to dynamically track changes in community infection. However, traditional prediction models consider fewer factors, and the spread of COVID-19 is influenced by several factors, such as population movement [8] , virus variants [9] , and city size [10] , which can affect the ability of COVID-19 to spread. Therefore, more advanced methods should be used in order to predict COVID-19 more effectively.…”
Section: Introductionmentioning
confidence: 99%